Comparative, reusability and regeneration study of potassium oxide-based catalyst in deoxygenation reaction of WCO - Hafriz R.S.R.M.; Nor Shafizah I.; Arifin N.A.; Maisarah A.H.; Salmiaton A.; Shamsuddin A.H. (Elsevier Ltd, 2023)
Calcination; Catalyst selectivity; Diesel engines; Potassium compounds; Pyrolysis; Silicon; Silicon compounds; Calcined dolomite; Deoxygenation reactions; Deoxygenations; Green diesels; K2O/SiO2 catalyst; Performance; Reusability & regeneration; Waste cooking oil; ]+ catalyst; Reusability